Chapter Scelta del topic e codificazione anaforica nelle composizioni argomentative in ceco L2 - PERISSUTTI, Anna Maria (Biblioteca di Studi Slavistici, 2016)
The research presented in the paper investigates the acquisition of L2 writing skills in Czech. It has been realized in the framework of Wrilab2, a European LLP project co-financed by the European Commission for the period 2014-2016. On the basis of data extracted from two corpora (the Czech learner corpus CzeSl and the Czech L1 corpus Český jazyk Literatura aneb studentský underground), the research compares the anaphoric codification strategies in Czech L1 and Czech L2 compositions.